(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article focuses on the changes that take place in the life insurance market in years 1991-2008, especiallyin the structure of this department according to the Gross Premium of the life insurance. The research was based on the literature search query, legal regulations in force in the whole investigated period as well as on the analysis and financial data included in the annual reports concerning life insurance market developed by the Board of Financial Supervision. In the research period the provisions of law were adjusted to the standards and requirements imposed by the European Union which re-sulted in creation of new life insurance companies in Poland, greater concentration level and change in the written gross premium of the life insurance market. Classical life insurance have lost their part for the benefit of the life insurance with capital founds until 2007. In 2008 according to the written gross premium. The life insurances were the biggest part of the life insurance structures.